An Analysis of Activity and Learning Outcomes of Elementary School Students in The New Normal Era - Faukhil Wardati (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article is motivated by the Covid-19 pandemic which has an impact on learning. The purpose of this article was to describe the activities and learning outcomes of class III students in theme 1 sub-theme 1 MI NU Tasywiquth Thullab Salafiyah in carrying out learning in the new normal era. This type of research is qualitative phenomenology, the data collection techniques used are observation and interviews, the subject and setting in this study there are six students and one third grade teacher, at school and at each student's home. The data analysis technique used is according to Milles & Huberman consists of collecting data, condensing data, presenting data, drawing and verifying conclusions. The result of this article is that all indicators of learning activities have not been implemented, indicators that have been implemented by students are proposing ideas and working independently. Meanwhile, indicators that have not been implemented are asking questions, providing ideas and suggestions, and expressing opinions. Student learning outcomes show that all learning objectives consist of aspects of knowledge, attitude aspect, and skills aspect have been seen in the six students.